2021
DOI: 10.3390/jof7020128
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of Cell Wall-Related Proteins of Different Yeasts

Abstract: Yeast cell walls have two major roles, to preserve physical integrity of the cell, and to ensure communication with surrounding molecules and cells. While the first function requires evolutionary conserved polysaccharide network synthesis, the second needs to be flexible and provide adaptability to different habitats and lifestyles. In this study, the comparative in silico analysis of proteins required for cell wall biosynthesis and functions containing 187 proteins of 92 different yeasts was performed in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
0
26
1
Order By: Relevance
“…There are extensive variations in yeast cell wall when comparing different fungal species and strains, such as α-glucans in addition to β- glucans, differences in concentration of chitosan, galactomannans and melanin [11]. Although cell wall composition among H. uvarum, P. kluyveri, C. intermedia and S. boulardii is comparable, it was demonstrated by Mateja et al [38] significant differences in their genera regarding patterns of GPI anchored and non-covalently attached proteins, as well as cell wall thickness, permeability, amounts of mannan and glucans. Thus, different responses induced in immune cells may be related to cell wall complexity and its components [39].…”
Section: Discussionmentioning
confidence: 99%
“…There are extensive variations in yeast cell wall when comparing different fungal species and strains, such as α-glucans in addition to β- glucans, differences in concentration of chitosan, galactomannans and melanin [11]. Although cell wall composition among H. uvarum, P. kluyveri, C. intermedia and S. boulardii is comparable, it was demonstrated by Mateja et al [38] significant differences in their genera regarding patterns of GPI anchored and non-covalently attached proteins, as well as cell wall thickness, permeability, amounts of mannan and glucans. Thus, different responses induced in immune cells may be related to cell wall complexity and its components [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, large amounts of galactose were detected in the polysaccharides. Therefore, we hypothesize that the bifunctional GAL10P in yeast is responsible for the absence of galactose in wild-type yeast polysaccharides ( Lozančić et al, 2021 ). However, it is difficult to explain the special structure of basidiomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…Pir phylogeny was inferred in MEGA 11 (Tamura et al, 2021) by applying to the 406 Pir homologues identified in Lozančić et al (2021) the maximum likelihood method and Dayhoff matrix-based model (Schwarz and Dayhoff, 1979). Positions with less than 95% site coverage were eliminated.…”
Section: Investigating Pir Genomic Loci and Phylogenymentioning
confidence: 99%